2023
DOI: 10.1038/s41598-023-39890-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated astrocytes and microglia markers are upregulated in mice fed high fat diet

Abstract: High-fat diet (HFD) is associated with Alzheimer’s disease (AD) and type 2 diabetes risk, which share features such as insulin resistance and amylin deposition. We examined gene expression associated with astrocytes and microglia since dysfunction of these cell types is implicated in AD pathogenesis. We hypothesize gene expression changes in disease-associated astrocytes (DAA), disease-associated microglia and human Alzheimer’s microglia exist in diabetic and obese individuals before AD development. By analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 95 publications
(101 reference statements)
0
10
0
Order By: Relevance
“… Sirkis et al (2023) explores the association of early-onset Alzheimer’s disease (EOAD) with specific peripheral immune signatures, and single-cell RNA sequencing identified significant expansion of a CD4 T cell termed interferon (IFN) signaling-associated gene (ISAG) hi T cells. Lin et al (2023) has explored the association between high-fat diet and AD and T2D. Analysis of single-cell RNA-seq (scRNA-seq) data indicated C4b is astrocyte-specific.…”
Section: Methods Of Identification Of Candidate Biomarkers For Admentioning
confidence: 99%
See 2 more Smart Citations
“… Sirkis et al (2023) explores the association of early-onset Alzheimer’s disease (EOAD) with specific peripheral immune signatures, and single-cell RNA sequencing identified significant expansion of a CD4 T cell termed interferon (IFN) signaling-associated gene (ISAG) hi T cells. Lin et al (2023) has explored the association between high-fat diet and AD and T2D. Analysis of single-cell RNA-seq (scRNA-seq) data indicated C4b is astrocyte-specific.…”
Section: Methods Of Identification Of Candidate Biomarkers For Admentioning
confidence: 99%
“…The altered expression of iron death-related DEGs affected the infiltration of specific immune cell types. Non-coding RNAs (ncRNAs) are involved in ferroptosis and AD progression, Tan et al (2023) identified 5 AD and ferroptosis-related hub genes, and constructed a novel ferroptosis-related signature models including mRNAs, miRNAs and lncRNAs. Deng et al (2022) screen correlative ferroptosis-related genes (FRGs) in the progress of AD by logistic regression.…”
Section: Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotypic shift was observable early during HFD feeding, even preceding substantial weight gain. Lin et al [ 133 ] elucidates the upregulation of disease-associated astrocyte (DAA) and microglia markers in response to an 12 w-HFD that are similar to the pathogenesis of Alzheimer’s disease. providing a direct link between dietary habits, neuroinflammation, and neurodegeneration.…”
Section: Obesity-induced Neuroinflammation: Phenotypes and Mechanismsmentioning
confidence: 99%
“…HFD-induced hypothalamic neuroinflammation, insulin resistance status, and glucolipid metabolism (173). HFD induces upregulation of hypothalamic potassium inwardly rectifying channel subfamily J member 2 Gene (Kcnj2), Complement 4b (C4b) and discoidin domain receptor 1 (Ddr1) and co-localizes with GFAP, and is therefore considered an early marker of obesity and diabetesrelated cognitive dysfunction (174). Secretion of inflammatory factors by astrocytes is associated with synaptic loss.…”
Section: Astrocyte Immunoreactivitymentioning
confidence: 99%